Crystal structure of 5-(1,3-dithian-2-yl)-2H-1,3-benzodioxole - Zukerman-Schpector, J.; Caracelli, I.; Stefani, H.A.; Gozhina, O.; Tiekink, E.R.T. (International Union of Crystallography, 2015)
In the title compound, C11H12O2S2, two independent but virtually superimposable molecules, A and B, comprise the asymmetric unit. In each molecule, the 1,3-dithiane ring has a chair conformation with the 1,4-disposed C atoms being above and below the plane through the remaining four atoms. The substituted benzene ring occupies an equatorial position in each case and forms dihedral angles of 85.62 (9) (molecule A) and 85.69 (8)° (molecule B) with the least-squares plane through the 1,3-dithiane ring. The difference between the molecules rests in the conformation of the five-membered 1,3-dioxole ring which is an envelope in molecule A (the methylene C atom is the flap) and almost planar in molecule B (r.m.s. deviation = 0.046 Å). In the crystal, molecules of A self-associate into supramolecular zigzag chains (generated by glide symmetry along the c axis) via methylene C - H⋯π interactions. Molecules of B form similar chains. The chains pack with no specific directional intermolecular interactions between them.